Europe's new state of welfare : unemployment, employment policies and citizenship / edited by Jørgen Goul Andersen [and three others]. - Goul Andersen, Jørgen (Policy Press, 2002)
It is often argued that the regulated labour markets, relatively generous social protection and relative wage equality of European welfare states has become counter-productive in a globalised and knowledge-intensive economy. Using in-depth analysis of employment, welfare and citizenship in a range of European states, this book challenges this view.